AN ANALYSIS OF SLANG TRANSLATION IN THE SUBTITLES OF "THE DEPARTED" MOVIE - Eku Baruna Graha, - (2010)
This study is entitled An Analysis of Slang Translation in the Subtitles of "The Departed" Movie. The study presents an analysis of slang types that are found in the movie, the subtitling strategies applied in subtitling the slang words and also the quality of slang translation in the subtitles of "The Departed" movie. This study employs a qualitative method in analyzing the data and a descriptive method in presenting the data. The findings were obtained through several steps: first, juxtaposing the written dialogues (English version) and the subtitle (Indonesian version) of the movie, second, collecting and classifying the slang based on Willis' classification (1964) and Feldman and Sourdot's classification (2008), third, determining the subtitling strategies of slang by using strategies proposed by Gottlieb (1992), fourth, judging the quality of slang translation by employing Barnwell's criteria judgment (1996) and finally, drawing the conclusion. The findings reveal that there were 146 slang items found in the movie. Referring to Willis' slang classification, there were 75 items (51.36%) of slang that gave new meanings to standard words and 71 items (48.63%) of slang that were new inventions or at least had only slight connection with the established words. Meanwhile, regarding to Feldman and Sourdot's slang classification, synonymy was the most applicable procedure with 56 items (38.35%). The findings also reveal that there were 29 items (19.86%) of lexical composition, 20 items (13.69%) of apocope and metaphor, 8 items (5.47%) of syntactic, 5 items (3.42%) of metonymy, 2 items (1.36%) of apheresis and assimilation and 1 items (0.68%) of derivation, doubling, abbreviation, and reversal. This study also shows that transfer was the most frequently used Gottlieb's subtitling strategies with 42 items (27.27%), followed by condensation with 30 items (19.48%), paraphrase with 27 items (17.53%), expansion and imitation with 18 items (11.68%), decimation with 9 items (5.84%), deletion with 5 items (3.24%), resignation with 3 items (1.94%), and transcription with 2 items (1.29%). In addition, based on the questionnaires given to the two reviewers including the writer, the results show that the quality of slang translation is in "Good" level. It was analyzed by using Barnwell's criteria judgment (1996) that focused on the accuracy, clarity and naturalness of translation . The findings of this study are expected to give a wider perspective about slang translation and classification. Hopefully this study is also supposed to contribute fresh ideas to further studies.